The Effects of Tobacco Smoking on the Body of Adolescents in the Prevention of Harmful Sports-Oriented Habits (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In the 21st century, almost a billion people who have failed to overcome their addiction to cigarettes, snuff, hookahs, cigars and smoking pipes may die from tobacco. Smoking in all its forms remains the main preventable cause of death worldwide. Tobacco kills between one third and half of the people who have been using it regularly for 15 years. Representatives of the World Association of Lung Diseases believe that by 2030, the number of deaths due to smoking will increase to 10 million people per year. Smokers, on the other hand, cannot give up cigarettes, about 80% would like to do so, but only 4 people out of 100 can. The revenues of governments from tobacco taxes are on average 5,000 times more than the funds they spend on tobacco control.